STRATEGI KOMUNIKASI PEMASARAN YAYASAN PENDIDIKAN AR RASYIID BINTARO DALAM MENINGKATKAN JUMLAH SISWA (PERIODE 2020-2022) - Dewi, Oktalia Winda; Octory, Gadis (MediaKom : Jurnal Ilmiah Komunikasi, 2024)
This research aims to identify and analyze the marketing communication strategies employed by Ar Rasyiid Bintaro Educational Foundation in increasing the number of students during the period 2020-2022. The research method used is a case study with data collection techniques based on primary data through observation and interviews, as well as secondary data from documentary studies. The data analysis method involves data reduction, data presentation, and drawing conclusions or verification. The results of the research indicate that in 2020, Ar Rasyiid Bintaro Foundation implemented a Word of Mouth-based marketing communication strategy. During the Covid-19 pandemic, the foundation successfully implemented a marketing communication strategy with a focus on a fun learning approach, a family-like atmosphere, and the utilization of social media and digital technology. This successfully increased the number of students and maintained the foundation's reputation. In 2022, the foundation quickly adapted to changes in the external situation and made changes in promotional tactics, including the use of social media, digital advertising, and special offers. The foundation's success in overcoming challenges and maintaining its appeal in the education market highlights the importance of flexibility, adaptability, and the role of social media and technology in developing effective marketing strategies.